Against Identity: a Positionalist Approach to Resisting Identity-Based Violence - (:unkn) unknown (My University, 2022)
I develop and defend a positionalist theory of identity as a basis from which to resist identity-based violence. On this account, identities are the social positions that individuals occupy due to belief that operate upon them. This contrasts with and is intended to replace the dominant intrinsicist model, which conceives of identity as something about individuals in and of themselves. Taking gender as a focal point, I develop three overarching positionalist kinds: monogyne, polygyne, and androgyne. I propose that additional sub-kinds (e.g. monogyne woman) be developed in order to more exactly track gender positionalities and the operational beliefs that produce them. I anticipate two objections against my positionalist account: the inclusion problem and the respect problem. I argue that positionalism can be used to reliably track the positionalities of individuals (addressing inclusion) and that including individuals into the intrinsicist kinds they identify with is an undesirable theoretical practice (addressing respect).
Keywords: Ethics; Identity; Justice; Philosophy; Social Metaphysics; Voss